IMPROVEMENT OF EXPERT ANALYSIS FOR ROAD TRAFFIC ACCIDENTS USING COMPUTER SIMULATION PROGRAMS - S. A. Azemsha; V. N. Galushko; S. V. Skirkovski (Наука и техника)
The existing methods for auto-technical expertise presuppose selection of some parameters on the basis of the expert’s intuition and experience. Type of a vehicle and its loading rate, road conditions are not taken into account also in the case when deceleration is to be determined. While carrying out the analysis it has been established that an application of special software makes it possible to improve significantly efficiency of the executed works directed on solution of the assigned tasks, to speed up calculation processes, to decrease qualitatively probability of arithmetic errors and provides the possibility to visualize results of the conducted investigations. Possibility of using various models for dynamic motion simulation and collision of vehicles (in the form of 3D-models) has been established in the paper. In such a case specific features of vehicle technical conditions, its loading rate and condition of roadway surface have been taken account in the paper. The given paper also permits to obtain a dynamic display of reconstructed accident mechanism in axonometric projection, to film video-clips when a camera is positioned at any spatial point: road, roadside, raised position, moving vehicle, driver's seat in the vehicle.The paper contains an analysis of possibilities of road traffic accident simulation programs, a statistical analysis that shows significance in differences between simulation results when various programs have been used. The paper presents initial data and results of vehicle speed calculation on the basis of braking track length which have been obtained with the help of road traffic accident express analysis (a classical approach) and PC-Crash when additional influencing factors are taken into account. A number of shortcomings have been revealed while analyzing the simulation results of the applied software. The shortcomings must be removed in the analyzed software products.On the basis of the executed analysis in respect of application of road traffic accident simulation programs it has been proposed to involve responsible and controlling authorities (State Automobile Inspectorate, expert institutions, insurance companies) for practical activity with the purpose to increase the objectivity of the result conclusions.